2011
DOI: 10.1002/hbm.21445
|View full text |Cite
|
Sign up to set email alerts
|

Fiber tract‐specific white matter lesion severity Findings in late‐life depression and by AGTR1 A1166C genotype

Abstract: Past work demonstrated that late-life depression is associated with greater severity of ischemic cerebral hyperintense white matter lesions, particularly frontal lesions. However, these lesions are also associated with other neuropsychiatric deficits, so these clinical relationships may depend on which fiber tracts are damaged. We examined the ratio of lesion to nonlesioned white matter tissue within multiple fiber tracts between depressed and nondepressed elders. We also sought to determine if the AGTR1 A1166… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 57 publications
(77 reference statements)
3
35
1
Order By: Relevance
“…Taylor et al (2009) reported significant increases in white matter lesion volume over a 2-year period in older adult men with the C1166 variant. A similar study from this group reported a modest association between the C1166 variant and enhanced lesion severity spanning multiple white matter tracts among nondemented elders both with and without depression (Taylor et al 2013). The results of the present study extend those of Taylor et al (2009Taylor et al ( , 2013 by demonstrating enhanced SH volume in a sample of clinically healthy (e.g., no evidence of clinical depression or dementia) older men and women.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Taylor et al (2009) reported significant increases in white matter lesion volume over a 2-year period in older adult men with the C1166 variant. A similar study from this group reported a modest association between the C1166 variant and enhanced lesion severity spanning multiple white matter tracts among nondemented elders both with and without depression (Taylor et al 2013). The results of the present study extend those of Taylor et al (2009Taylor et al ( , 2013 by demonstrating enhanced SH volume in a sample of clinically healthy (e.g., no evidence of clinical depression or dementia) older men and women.…”
Section: Discussionsupporting
confidence: 79%
“…A similar study from this group reported a modest association between the C1166 variant and enhanced lesion severity spanning multiple white matter tracts among nondemented elders both with and without depression (Taylor et al 2013). The results of the present study extend those of Taylor et al (2009Taylor et al ( , 2013 by demonstrating enhanced SH volume in a sample of clinically healthy (e.g., no evidence of clinical depression or dementia) older men and women. Furthermore, no studies have examined the functional relationship between A1166C, SH, and cognition in a healthy population.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Many magnetic resonance imaging (MRI) studies have shown that LLD is associated with demyelinating lesions, which are seen as white matter hyperintensities (WMHs) on MRI (Chen et al, 2006;Firbank et al, 2012;Herrmann et al, 2008;Krishnan et al, 2004;Taylor et al, 2005Taylor et al, , 2013. In older adults, the etiology of these lesions is largely thought to be related to ischemic disease, but other neuropathologic processes may also have a role.…”
Section: Introductionmentioning
confidence: 99%
“…LLD is associated with increased WML severity in the cingulum bundle, uncinate fasciculus, and superior longitudinal fasciculus (Dalby et al, 2010; Sheline et al, 2008; Taylor et al, 2013b). Similar findings are reported in these tracts using diffusion tensor imaging to measure fiber tract structural integrity in both late-life (Sexton et al, 2012; Taylor et al, 2007) and midlife depression (Zhang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%